Stress concentrations in composites laminates - Ang, Bo Jia (2017)
This study determines the stress analysis of orthotropic unidirectional composites lamina with induced center single circular hole and double circular holes under static uniform tensile loading using the Boundary Element Method. Two materials used in the analysis are Aramide Reinforced Aluminium Laminate and Glass Laminate Aluminium Reinforced Epoxy. Results of the stress distributions, stress concentration locations and magnitude and failure function around the circular hole were presented. The stress analysis were conduction under parameter variations such as lamina fibre orientations, diameter of hole and distance between double holes. It was observed in orthotropic composites lamina, the high stress concentrations locations may not necessarily coincides with the failure locations.